2020
DOI: 10.3390/su12229711
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Technological Capability of a Host Country on Inward FDI in OECD Countries: The Moderating Roles of Institutional Quality

Abstract: This empirical study explores the impacts of technological capability on inward foreign direct investment (FDI) with the moderations of institutional quality. We extend the existing literature by contributing the dynamic links between technology trade and institutional quality by using the panel data of 35 Organization for Economic Cooperation and Development (OECD) countries between 2000 and 2015. Based on fixed-effects regression, our results show that there is a U-shape relationship between the net technolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 61 publications
1
3
0
Order By: Relevance
“…The measurement results in both GMM and PVAR methods with two models with and without the influence of institutions, both show a positive impact of technological capacity on economic development. The estimated coefficient of TC has a positive value at a 1% of significant level, which is consistent with the study of Kim and Choi (2020) [36] on the influence of technological capacity on economic development.…”
Section: Technological Capability (Tc)supporting
confidence: 89%
“…The measurement results in both GMM and PVAR methods with two models with and without the influence of institutions, both show a positive impact of technological capacity on economic development. The estimated coefficient of TC has a positive value at a 1% of significant level, which is consistent with the study of Kim and Choi (2020) [36] on the influence of technological capacity on economic development.…”
Section: Technological Capability (Tc)supporting
confidence: 89%
“…The growing interest in institutional and political development economics issues has resulted in detailed research on the factors influencing institutional quality [160]. The current study investigated the nexus of institutional quality-led tourism and exposed positive connections in empirical assessment, which is in line with Delgado and McCloud [161], Kim and Choi [162], Qamruzzaman, Tayachi, Mehta, and Ali [18]. Because of good institutional quality, the foreign direct investment (FDI) inflows are strong, and foreign direct investment (FDI) volatility is low.…”
Section: Discussionmentioning
confidence: 71%
“…A large number of studies related to determinants of FDI are focused on regional institutional quality (IQ) investigations. As an examples ,emerging economies [90] ,developed and developing countries [91,92] , OECD countries [93], and Asian economies [94,95]. Recent empirical research has concluded that improved institutional quality in countries is more likely to attract FDI inflows [91,93,[96][97][98][99][100][101][102][103][104][105][106][107][108][109][110].…”
Section: Literature Reviewmentioning
confidence: 99%
“…As an examples ,emerging economies [90] ,developed and developing countries [91,92] , OECD countries [93], and Asian economies [94,95]. Recent empirical research has concluded that improved institutional quality in countries is more likely to attract FDI inflows [91,93,[96][97][98][99][100][101][102][103][104][105][106][107][108][109][110]. Institutional variables, notably corruption, political constraints, and property rights protection, are major determinants of FDI inflows [111].…”
Section: Literature Reviewmentioning
confidence: 99%